God's names, attributes and meanings of God And atheism in i (Journal of the College of Basic Education, 2022)
The subject of this study is related to an explanation of the efforts of a contemporary scholar in the Islamic faith, the distinguished scholar Professor Dr. Wahba Al-Zuhaili (may God have mercy on him), shedding light on his efforts in the Islamic faith, showing the characteristics of his personality and showing his scientific standing on the level of the Islamic world in general. The importance of this study stems from the importance of its topic, namely the doctrine of nouns and adjectives, and this importance increases in explaining how Imam al-Zuhaili presented the doctrinal issues and his style in them and the extent of his influence on Muslims and their influence with it. And that is through his attention to the doctrinal issues and their presentation in a clear, easy and appropriate manner, and in it he showed the efforts of contemporary scholars to innovate in the smoothness of the method, the accuracy of the presentation and the seriousness in his presentation of his method, especially in the issue of names and attributes, so the role of these contemporary scholars should be highlighted, and their effects in the Islamic community should be shown. On the authority of many scholars of previous eras, and at the forefront of them was the fundamentalist scholar, the exegete, the jurist, the scholar, the scholar, Prof. Dr. Wahba al-Zuhaili (may God have mercy on him), who translated some of his books on exegesis and jurisprudence into more than one language. For researchers in our time, who are dedicated to the light of the Qur’an, the realization of truth, and the elimination of falsehood, who are the link between the efforts of the former and the contemporary. The research consisted of an introduction, a conclusion, and six discussions. The first was to explain the meaning of the name and the adjective in the language and convention, the second: what is meant by goodness in the names of God Almighty, the third: the meanings of the names of the Most High, and the fourth: the rational evidence for the attributes of God Almighty, the fifth was the informative attributes, and the sixth Atheism in the names of God Almighty.Praise be to God, Lord of the worlds, and may God bless our master Muhammad and his family and companions.